2013
DOI: 10.1021/ol401066j
|View full text |Cite
|
Sign up to set email alerts
|

Kleinhospitines A–D, New Cycloartane Triterpenoid Alkaloids fromKleinhovia hospita

Abstract: Kleinhospitines A-D, four unprecedented cycloartane triterpenoid alkaloids possessing a spiro α,β-unsaturated γ-lactamlactone side chain, were isolated as two mixtures of C-23 epimers from Kleinhovia hospita. Kleinhospitines C and D represent the first examples of naturally occurring cycloartane triterpenoids with a 9α,10α-cyclopropyl ring. The structures and absolute configurations were determined on the basis of spectroscopic analyses and comprehensive quantum chemical calculations. The two mixtures showed h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 12 publications
1
28
0
3
Order By: Relevance
“…The 1 H-NMR spectrum of 1 (Table) displayed two intercoupling olefinic doublets assignable to the a,b-unsaturated ketone of ring A at d(H) 6 group, probably in the side chain. 350 nm (contributed by excited state 1) indicated that this effect is determined by configurations of ring A and the cyclopropane ring, which is in consistent with our previous interpretation [3]. The C-atom signals of the a,b-unsaturated g-lactone group of ring F appeared at d(C) 171.4, 144.6, and 133.6.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The 1 H-NMR spectrum of 1 (Table) displayed two intercoupling olefinic doublets assignable to the a,b-unsaturated ketone of ring A at d(H) 6 group, probably in the side chain. 350 nm (contributed by excited state 1) indicated that this effect is determined by configurations of ring A and the cyclopropane ring, which is in consistent with our previous interpretation [3]. The C-atom signals of the a,b-unsaturated g-lactone group of ring F appeared at d(C) 171.4, 144.6, and 133.6.…”
supporting
confidence: 91%
“…-Before our first discovery of cycloartane triterpenoids with spiro side chains from Kleinhovia hospita (Annonaceae) in 2009, only a few fatty acids and flavonoids had been reported from this medicinal plant [1]. Moreover, our re-investigation of this medicinal plant in 2012 resulted in the isolation of unprecedented cycloartane-triterpenoid alkaloids possessing spiro a,b-unsaturated g-lactamlactone side chains and 9a,10a-cyclopropyl rings [3]. Moreover, our re-investigation of this medicinal plant in 2012 resulted in the isolation of unprecedented cycloartane-triterpenoid alkaloids possessing spiro a,b-unsaturated g-lactamlactone side chains and 9a,10a-cyclopropyl rings [3].…”
mentioning
confidence: 99%
“…[100] Sodium isethionate is used on an industrial scale in electroplating baths and for the preparation of tensides, so it is commercially available at low cost. Ethylvinyl sulfonate (19a) [101] and N-benzylvinylsulfonamide (19b) [102] were synthesized from 21 by reaction with ethanol or benzylamine, respectively, as described previously in the literature. Tertiary vinylsulfonamide 19c was synthesized by methylation of 19b under basic conditions (Scheme 2).…”
Section: Optimization Of Reaction Conditionsmentioning
confidence: 99%
“…During our continuous research on hepatoprotective cycloartane triterpenoids from these plants, two dimeric 3‐prenylindole alkaloids, cimicifoetones A ( 1 ) and B ( 2 ) (Figure ), bearing a unique alkyl‐aromatic [4+2] Diels–Alder cycloaddition‐derived indole‐benzoindolequinone skeleton, were accidentally discovered as black pigments of C. foetida . Herein, we describe their isolation, structural elucidation, cytotoxic activities, and action mechanisms on tumor cell apoptosis.…”
Section: Figurementioning
confidence: 99%